Gestos na aquisição da língua inglesa em contexto bilíngue: uma perspectiva multimodal. - Peixoto, Simone Frye (2020)
Investigative studies on gesture in second language acquisition within a bilingual context mobilize a debate between multimodality theoretical perspectives and applied linguistics, placing the research on relevant and fruitful foundations, anticipating the enrichment of both areas. Therefore, the purpose of this dissertation is to analyze gesture production as a multimodal resource integrated into the process of acquisition and development of a second language. Specifically, the study aimed to identify the gestures used by the children and to verify their incidence in the acquisition of English as a second language within a bilingual context; to analyze the role of gestures in spoken English; and, finally, to compare the types of gestures and their role in relation to Portuguese and English spoken languages. The scientific research lies on the multimodal language perspective, in which gesture and vocal production comprise the same array of signification, according to Kendon 1982; 2017), McNeill (1985; 1992; 2000), Goldin-Meadow (2003; 2009; 2016), Stam (2006; 2007; 2014), Fonte (2011; 2014); and on second language acquisition and bilingualism studies carried out by Grosjean (1982; 2010; 2013; 2014; 2018), Gullberg (2006; 2012), Moraes (2012; 2018), Tellier (2005; 2008), Stam (2008), amongst others. Methods were supported by a cross-sectional case study based on qualitative approach whose sample includes a 5-year-old child. Data were collected through video recordings made with the cell phone by the child’s own family due to the social isolation resulting from COVID-19 pandemic. The research comprised the analysis of home videos produced during instructional as well as free activities, displaying bilingual (English-Portuguese) child - parent/relative interactions. Videos were transcribed with the help of software tool ELAN (Eudico Linguistic Annotator). Transcription and analysis criteria were also considered in the light of the multimodal perspective of language functioning. Research data revealed gesture occurrence in an equivalent productive amount in English and in Portuguese, with major incidence of deictic gestures in comparison to beats and iconic gestures. Regarding the role of gestures in both languages, they functioned, in general terms, as linguistic organizers, validating its impact on speech fluency and flow. Results will serve as indicators of multimodal language functioning, signs of language processing, as well as question demystifiers concerning linguistic production in the acquisition of English as a second language in the context of bilingual education, as the belief that L2 prevents L1 development. Expectations concerning the scientific contribution lays its foundations in the findings related to bilingualism and multimodality. Indirectly, pervading teacher’s awareness and training as to have them take on a new look about the theme and substantiate their practice, whose route will benefit the students, the social contribution of the study is consolidated.